The Mind addiction - Freeth, Martin; Raven, Keith (The Mind series, 1988)
Experiments with persons suffering from heroin, alcohol, nicotine, food or gambling addictions provide unusual insight into the nature of the mind. In this episode, scientists explain the reasons for the pain of withdrawal. Recent studies on the mind's capacity for chemical dependency are detailed, revealing a complex and delicate balance within a brain.